Surveillance of the Remaining Nodules after Resection of the Dominant Lung Adenocarcinoma is an Appropriate Follow-Up Strategy - Castiglioni, Massimo; Louie, Brian E.; Wilshire, Candice L.; Farivar, Alexander S.; Aye, Ralph W.; Gorden, Jed; Horton, Matthew P.; Vallières, Eric (Frontiers in Surgery, 2015)
Introduction: Adenocarcinomas, commonly present as a dominant lesion (DL) with additional nodules in the ipsilateral or contralateral lung. We sought to determine the fate and management of the secondary nodules and to assess the risk of these nodules using the Lung CT Screening Reporting and Data System (Lung-RADS) criteria and the National Comprehensive Cancer Network (NCCN) Guidelines to determine if surveillance is an appropriate strategy. Methods: We retrospectively evaluated patients with lepidic growth pattern adenocarcinoma and secondary nodules from 2000 to 2013. Risk assessment of the additional lesions was completed with a simplified model of Lung-RADS and NCCN-Guidelines. Results: Eighty-seven patients underwent resection of 87 DLs (Group 1) concurrently with 60 additional pulmonary nodules (Group 2), while 157 non-DLs were radiologically surveyed over a median follow-up time of 3.2 years (Group 3). Malignancy was found in 29/60 (48%) nodules in Group 2. Whereas, only 9/157 (6%) of the lesions in Group 3 enlarged, 4 of which (2.5% of total) were found to be malignant, and then treated, while the remaining nodules continued surveillance. After applying the Lung-RADS and NCCN simplified models, nodules in Group 2 were at higher risk for lung cancer than those in Group 3. Conclusion: In patients with lepidic growth pattern adenocarcinoma associated with multiple secondary nodules, surveillance of the remaining nodules, after resection of the DL, is a reasonable strategy since these nodules exhibited a slow rate of growth and minimal malignancy. In contrast, nodules resected from the ipsilateral lung at the time of the DL, harbor malignancy in 48%. Risk assessment models may provide a useful and standardized tool for clinical assessment of pulmonary nodules.